OC-022 MAINTAINING AN ELECTIVE ABDOMINAL WALL RECONSTRUCTION SERVICE DURING THE COVID 19 PANDEMIC. (13th October 2022) - Dixon, S; Benson, A; Kalaiselvan, R; Kanwar, S; Samad, A; Pritchard-Jones, R; West, C; Scott, M
Abstract: Aim: Elective surgery services suffered significantly due to the COVID-19 pandemic. The aim of this study was to analyse the impact and outcomes of abdominal wall reconstruction (AWR) performed during the COVID-19 pandemic, assessing safety and sustainability. Material and Methods: A retrospective review of all patients undergoing AWR in a single NHS trust, multiple surgeons, between 23 rd March 2020 and 22 rd March 2022, the 2 years following U.K. Government imposed lockdown, was undertaken and compared with the pre-pandemic AWR activity. Procedures were initially undertaken at a cold site and when demonstrated to be safe, main site operating restarted. The primary outcome was 90 day mortality, secondary outcomes of COVID-19 infection within 7 days, length of stay, critical care requirement, and complication rate. Results: In the study period, 173 patients underwent AWR, compared with 99 cases in a single year preceding lockdown. 90 day mortality rate was zero. No patients returned positive COVID tests to the trust within 7 days of AWR, and no patients were readmitted for COVID related symptoms. Critical care admission was required in 7 patients, 3 of these were planned admissions pre-operatively. The surgical site occurrence rate was 9.8% (17), infection 5.8% (10), seroma 2.3% (4) and haematoma 1.7% (3). There were no recurrences reported, with follow up ranging between 1 and 18 months. Conclusion: Continuing AWR services during the COVID pandemic is feasible and safe. Peri-operative COVID infection rates are low, critical care requirements minimal, and there is no impact on patient morbidity or mortality.